Forage biomass and water storage of cactus pear under different managements in semi-arid conditions - Lopes,Marcos Neves (2021)
ABSTRACT Forage biomass production and water storage (WS) was evaluated in cactus pear cv. Gigante fertilized with combinations of nitrogen (10, 70, 100, 130, and 190 kg ha−1 yr−1 N) and phosphorus (10, 70, 100, 130, and 190 kg ha−1 yr−1 P2O5) in annual (AH) and biennial (BH) harvest frequencies, in Quixadá and Tejuçuoca, Brazil. A randomized complete block design was used in a split-plot arrangement with four replications. In Quixadá, the maximum total forage biomass (TFB) recorded in the AH was 3,522.9 kg ha−1 yr−1 for the N/P2O5 combination of 134.6/190.0 kg ha−1 yr−1, and in the BH, the maximum TFB of 1,583.2 kg ha−1 yr−1 was recorded for the N/P2O5 combination of 114.6/136.8 kg ha−1 yr−1. In Tejuçuoca, the maximum TFB recorded in the AH was 9,783.0 kg ha−1 yr−1 for the N/P2O5 combination of 137.7/190.0 kg ha−1 yr−1, and in the BH, the maximum TFB of 12,124.0 kg ha−1 yr−1 was recorded for the N/P2O5 combination of 190.0/56.8 kg ha−1 yr−1. In Quixadá, the maximum WS recorded in the AH was 39.1 kg ha−1 mm−1 for the N/P2O5 combination of 161.0/190.0 kg ha−1 yr−1, and in the BH, the maximum WS of 11.3 kg ha−1 mm−1 was recorded for the N/P2O5 combination of 113.5/158.7 kg ha−1 yr−1. In Tejuçuoca, the maximum WS recorded in the AH was 196.1 kg ha−1 mm−1 for the N/P2O5 combination of 190.0/190.0 kg ha−1 yr−1, and in the BH, the maximum WS of 265.5 kg ha−1 mm−1 was recorded for the N/P2O5 combination of 190.0/10.0 kg ha−1 yr−1. To achieve the persistence and longevity of the cactus pear cv. Gigante, the management with BH and fertilization with the N/P2O5 combination of 114.6/136.8 kg ha−1 yr−1 (in regions similar to Quixadá) and N/P2O5 combination of 190.0/56.8 kg ha−1 yr−1 (in regions similar to Tejuçuoca) is recommended.